Is increasing productivity COVID-19's silver lining? - Joel Blit (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2020)
Recent evidence for the U.S. suggests that recessions play a crucial role in promoting automation and the reallocation of productive resources, which in turn increase aggregate productivity and lead to a higher standard of living. I present evidence suggesting that the same is true in Canada. In particular, since the beginning of the information and communications technology revolution, fully all of the Canadian decline in routine job employment occurred during the three recessions. A similar dynamic is likely to transpire during the COVID crisis, and in fact is likely to be more pronounced due to the scale of the recession and the health-related incentives to automate. By constructing industry-level measures of worker exposure to COVID and the fraction of routine employment, I show that the retail, construction, manufacturing, wholesale, and transportation industries are likely to experience the biggest transformations. In these industries, government attempts to maintain the status quo will only delay the process of restructuring. Instead, policies should embrace change and support workers through the transition.
Keywords: E32; J24; O38; 330; COVID-19; recessions; productivity; innovation; automation